Citalopram restores short-term memory deficit and non-cognitive behaviors in APP/PS1 mice while halting the advance of Alzheimer's disease-like pathology. (15th March 2018) - Zhang, Qin; Yang, Chen; Liu, Tianyao; Liu, Liang; Li, Fen; Cai, Yulong; Lv, Keyi; Li, Xin; Gao, Junwei; Sun, Dayu; Xu, Haiwei; Yang, Qingwu; et al.
Abstract: Alzheimer's disease (AD) is the most common cause of dementia. In addition to cognitive impairments, deficits in non-cognitive behaviors are also common neurological sequelae in AD. Here, we show that complex behavioral deficits in 7-month-old APPswe/PSEN1dE9 (APP/PS1) mice include impairments in object recognition, deficient social interaction, increased depression and buried marbles. Citalopram, one of the selective serotonin reuptake inhibitors (SSRIs), ameliorated the amyloid deposition in AD patients and transgenic animal models. After treatment for 4 weeks, citalopram rescued the deficits in short-term memory, sociability and depression in these mice. Further immunohistochemical analysis showed chronic citalopram treatment significantly attenuated β-amyloid deposition and microglial activation in the brains of APP/PS1 mice as demonstrated previously. Parvalbumin (PV) interneurons, which are the primary cellular subtype of GABAergic neurons and considered indispensable for short-term memory and social interaction, also contributed to the progress of depression. Additionally, we found the citalopram could significantly increase the PV-positive neurons in the cortex of APP/PS1 mice without alteration in the hippocampus, which might contribute to the improvement of behavioral performance. Our findings suggest that citalopram might be a potential candidate for the early treatment of AD. Highlights: Citalopram could restore short-term memory deficit and non-cognitive behaviors in APP/PS1 mice. Citalopram could inhibit the microgliosis and β-amyloid deposition in cortex and hippocampus of APP/PS1 mice. Citalopram could increase cortical parvalbumin-positive neurons without alteration in hippocampus in APP/PS1 mice.